The effects of financial factors on takaful demand in Malaysia - Mohamed Dahlan, Ibrahim; Fauzilah, Salleh; Zainudin, Awang (2015)
This paper offers a theoretical framework for studying the effects of financial factors, i.e. leverage, growth, bankruptcy, tax, and other variables on Takaful (Islamic insurance) demand. Data were collected from three Takaful operators and the financial reports from the Companies Commission of Malaysia (SSM), including 278 small and medium-sized enterprises (SMEs) for this study. AMOS version 20, a variance-based Structural Equation Modelling (SEM), was used to analyse the data as well as to test the research hypotheses. The outcomes show that financial factors could be a major predictor of Takaful demand at least from the SMEs’ perspective. Financial factors were found to be positively affected by leverage, growth, bankruptcy, and taxes. The implications of these findings are discussed and recommendations for future research are provided.